Background image reconstruction using random frame sampling and logical bit operations - VARIAN SHERWIN, CHU (Archīum Ateneo, 2013)
This study explored a possible algorithm for background image reconstruction that uses bit operations and frame sampling. The algorithm followed some principles of the Teknomo-Fernandez (TF) Algorithm that is currently limited to 3 sample frames per proce